State of Cultural Heritage Sites of Uzbekistan in the Soviet Period - Rasulov Ma’murjon Foziljonovich (Genius Journals, 2023)
Based on rich factual material, the article reveals some aspects of the protection and use of historical and cultural monuments of the Republic of Uzbekistan, the attitude to them during the Soviet regime. The archival materials of the Soviet system and its dominant communist ideology reveal a nihilistic approach to the heritage of ancestors. The article gives many facts that as a result of incorrect use of engineering communications the state of historical monuments was severely damaged. Besides, based on documentary sources it is proved that the pillars lost their historical value as a result of using them not for their intended purpose (as clubs, cinemas, atheistic museums, restaurants, hotels, warehouses, cattle yards, prisons, etc.) and natural and anthropogenic factors.
Keywords: architectural monuments; madrasahs; mosque; mausoleum